Atmospheric inputs of Ag and Tl to the arctic: comparison of a high resolution snow pit (AD 1994-2004) with a firn (AD 1860-1996) and an ice core (previous 16,000 yr) - Krachler, Michael; Zheng, Jiancheng; Fisher, David; Shotyk, William (The science of the total environment, 2008)
Applying strict clean room techniques and sector field ICP-MS, a total of 567 ice and snow samples from Devon Ice Cap, Arctic Canada, have been analysed for silver (Ag) and thallium (Tl), providing a continuous record of atmospheric deposition of both elements for the past ~16,000 yr. Concentrations of Ag and Tl ranged from 0.02 to 5.84 pg/g and from 0.03 to 3.40 pg/g, respectively. The natural Tl/Sc background ratio established with ice samples dating between 10,590 and 15,010 yr BP, amounted to 0.11±0.03 which is in good agreement with the corresponding value of 0.107 reported for the Upper Continental Crust (UCC). The Ag/Sc background ratio in ice (0.09±0.06), in turn, is much more variable and ~10-times higher than UCC values. The high temporal resolution provided by 45 samples from the 5 m snow pit representing the period AD 1994 to 2004, revealed the greatest elemental concentrations as well as accumulation rates during the winter months when air masses reach the Arctic predominantly from Eurasia. The greatest Sc concentrations, however, are also found during winter months which clearly reflect strong seasonal variations in atmospheric dust inputs. Enrichment factors calculated for both elements (Ag, Tl) using Sc show contrasting behaviours, with the maximum EF for Tl (up to 48) during summer when air masses arriving to the Arctic are predominantly from North America, probably reflecting coal burning, base metal mining and smelting. The greatest enrichments of Ag (up to 17), on the other hand, tend generally to be found in winter, although some enrichment maxima corresponding to summer months are also seen. While modern Ag EF are comparable to those corresponding to ancient (back to ca. 3 k yr) anthropogenic activities, modern Tl EF clearly exceed the impact of Medieval, Roman and Greek/Phoenician civilization. Accumulation rates during the past decade have been variable (mean 36 and 130 ng/m2/yr for Ag and Tl, respectively), but the trend is clearly in decline. Based on the best estimate of natural inputs, more than 80% of the Ag and 90% of the Tl supplied to the Arctic today (AD 1994-2004) are derived from anthropogenic sources.
Gesehen am 28.09.2020